Influence of Dietary Supplementation of Organic Acids, Probiotics and Their Combinations on Growth, Carcass Traits and Serum Parameters in Broiler Chicken - Srinivas, Gurram; Swathi, B.; Raju, S.; Tungani, Ravi (Indian Journal of Animal Nutrition, 2018)
The aim of the present study was to investigate the effect of dietary supplementation of probiotics, organic acids and their combination on the performance of broiler chicken. For this, day-old commercial male broiler chicks (120 No.) were randomly divided into four groups with six replicates of five birds each. The groups consisted of a control diet (flavomycin 650 g/tonne; T1), probiotics (Protexin @ 500 g/tonne; T2), commercial organic acid (Biotronic SE @ 3 kg/ton; T3) and combination of probiotics + acidifier (T4) at theirrespective inclusion rates and the study continued for 42 days. The weight gains and FCR was better (P